Ze studiów nad dworem w Poddębicach - Kajzer, Leszek (Acta Universitatis Lodziensis. Folia Archaeologica, 1982)
The country manor at Poddębice (Sieradz Province) situated about 40 kms north-west of Łódź is considered to be one of the most interesting Renaissance and manneristic rural residences in Poland. The article, based on discovery of unknown archival materials concerning the manor, is an attempt at critical evaluation of previous theses as regards the founder of the manor and chronology of stages in its reconstruction. According to generally accepted view the manor was built between 1610-1617 at the initiative of Zygmunt Grudziński, a voivode of Rawa District. In the second half of 17th century, it was assumed, took place a rebuilding of the manor in the course of which a loggia was covered with a wall, side gables were rebuilt and tower extended. In the first half of 13th century the Poddębice estate was to pass to the Zakrzewski family, who – it was supposed – in 1832 built a seven-sided chapel adjoining the main building. The manor was submitted to full reconstruction and expansion about 1873. In the light of the archival data from the period of 1690-1773 it appears that during this time there were not carried any bigger construction works in the manor. This information combined with a bad state of repair of the manor described in information from 1690 seems to undermine a thesis that the manor was rebuilt in the second half of 17th century.